Classification of subdural hematomas: proposal for a new system improving the ICD Coding Tools - Langlois, Anne-Marie; Touchette, Charles J.; Mathieu, David; Iorio-Morin, Christian (Frontiers in Neurology, 2023)
Background The International Statistical Classification of Diseases (ICD) classifies subdural hematoma (SDH) as traumatic or non-traumatic. In clinical settings, however, SDH is typically described as either acute or chronic. Objective The goal of this study was to assess how the ICD Coding Tools captures the clinical terminology and propose an improved classification that would increase the system’s usefulness in administrative, statistical and research applications. Methods We performed a retrospective analysis of patients who presented to our center with an ICD diagnostic code for either traumatic or non-traumatic SDH. A qualitative analysis of patients’ charts was performed to identify elements relevant to management and prognosis, following which a meeting between expert investigators was held to elaborate a new classification of SDH. Imaging from all patients was then reviewed and cases were reclassified according to our proposed system. Results A total of 277 SDH cases were included. Themes documented in the charts included chronicity, etiology, side and symptoms. We created a new classification which distinguishes acute SDH (aSDH) from membrane-associated SDH (mSDH). aSDH were further divided into traumatic aSDH (taSDH) and non-traumatic aSDH (ntaSDH), while mSDH were divided into acute on chronic (a/cSDH), subacute (sSDH) and chronic (cSDH) categories. Conclusion The ICD coding system correctly identifies taSDH and ntaSDH. However, it remains non-specific for mSDH. We propose this new SDH classification system to better capture chronicity and etiology – factors felt to impact management and prognosis.